Determinants of Healthy Puberty among Adolescents with Intellectual Disabilities: A Cross-Sectional Study in Indonesia - Norma Jeepi Margiyanti; Hardisman Hardisman; Alfan Miko; Amel Yanis (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Healthy puberty is a critical developmental phase requiring appropriate biological, psychological, and social adaptation, particularly for adolescents with intellectual disabilities who may experience limitations in cognitive and adaptive functioning. These limitations can affect their ability to understand bodily changes, maintain personal hygiene, and engage in appropriate social behavior during puberty. This study aimed to identify factors associated with healthy puberty behavior and to determine the strongest bivariate association among adolescents with intellectual disabilities. A quantitative analytic study with a cross-sectional design was conducted involving 32 adolescents selected using purposive sampling. Data were collected using a structured questionnaire assessing knowledge about puberty, attitudes toward puberty, health status, parental role, and healthy puberty behavior. Data were analyzed using univariate and bivariate statistical tests. The results showed that knowledge about puberty (p = 0.036; OR = 5.76) and parental role (p = 0.006; OR = 9.00) were associated with healthy puberty behavior. Health status showed a borderline association (p = 0.050; OR = 4.58), while attitudes toward puberty were not associated (p = 0.492). In conclusion, knowledge and parental role are important factors related to healthy puberty behavior among adolescents with intellectual disabilities, with parental role showing the strongest association. These findings highlight the importance of caregiver involvement in supporting adolescents during puberty. However, the small sample size limits the generalizability of the results.